Pengaruh Human Capital Dan Employee Engagement Terhadap Produktivitas Kerja Karyawan (Studi Kasus Pada Bea Cukai Kanwil Jatim II) - Miftahul Ulum; Muhammad Mansur; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine the effect of Human Capital and Employee Engagemet on Employee Work Productivity (case study on employees of Customs and Excise Regional Office of East Java II). The number of samples 70 in this study. In analyzing the data this study was assisted with SPSS version 25. The analysis used was the instrument test, multiple linear analysis test, class assumption test, hypothesis test.The results of this study partially concluded that there was a negative effect between Human Capital variables on Employee Work Productivity while positive effects between Employee Employee variables on Employee work Productivity and simultaneously concluded there was an influence between Human Capital variables and Employee Engagemets on Employee Work Productivity.Keywords: Human Capital, Employee Engagement, Employee Work Productivity